2014
DOI: 10.1177/1938640014548420
|View full text |Cite
|
Sign up to set email alerts
|

Driving Reaction Times in Patients With Foot and Ankle Pathology Before and After Image-Guided Injection

Abstract: Therapeutic, Level II: Prospective Comparative Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…Most studies used a crosssectional study design (n5 15, 68.1%). Four studies were controlled clinical trials, 30,38,42,49 2 studies used a prospective cohort design, 3,13 and one used a retrospective cohort design that involved registry data from a hospital emergency department. 39 The mean age of the participants ranged from 33 to 69 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies used a crosssectional study design (n5 15, 68.1%). Four studies were controlled clinical trials, 30,38,42,49 2 studies used a prospective cohort design, 3,13 and one used a retrospective cohort design that involved registry data from a hospital emergency department. 39 The mean age of the participants ranged from 33 to 69 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four studies (67%) found no differences in response time between drivers with CP and healthy controls. 6,47,49,58 However, 2 studies (44%) reported that drivers with CP have longer response times to hazardous events compared with healthy controls. 30,42 The considerable variability between study designs and differences in pain magnitude of participants with CP in different studies make interpretation difficult.…”
Section: Operational Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after surgery and joint prostheses, restrictions in fitness to drive may persist for some time. For example, Jordan and colleagues [186] found that after a knee joint replacement, the braking time was prolonged and that the initial values before the operation were only reached again after six weeks. Patients should therefore not restart driving until six weeks after knee joint surgery.…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
“…The BRT is a measure of cognitive and psychomotor performance and has been used in traffic accident prevention research to assess driving capability in various populations [10][11][12]. BRT is defined as the time interval between the appearance of an unexpected road event (the stimulus) and the complete execution of an emergency stop.…”
Section: Introductionmentioning
confidence: 99%